Prevalence and Loads of Fecal Pollution Indicators and the Antibiotic Resistance Phenotypes of Escherichia coli in Raw Minced Beef in Lebanon - Issmat I. Kassem; Nivin A Nasser; Joanna Salibi (Foods, 2020)
Meat is an important source of high biological value proteins as well as many vitamins and minerals. In Lebanon, beef meats, including raw minced beef, are among the most consumed of the meat products. However, minced beef meat can also be an important source of foodborne illnesses. This is of a major concern, because food safety in Lebanon suffers from well-documented challenges. Consequently, the prevalence and loads of fecal coliforms and Escherichia coli were quantified to assess the microbiological acceptability of minced beef meat in Lebanon. Additionally, antibiotic resistance phenotypes of the E. coli were determined in response to concerns about the emergence of resistance in food matrices in Lebanon. A total of 50 meat samples and 120 E. coli isolates were analyzed. Results showed that 98% and 76% of meat samples harbored fecal coliforms and E. coli above the microbial acceptance level, respectively. All E. coli were resistant to at least one antibiotic, while 35% of the isolates were multidrug-resistant (MDR). The results suggest that Lebanon needs to (1) update food safety systems to track and reduce the levels of potential contamination in important foods and (2) implement programs to control the proliferation of antimicrobial resistance in food systems.